The impact of the Riau Malay culture e-module on high school students’ understanding of self-identity values: Study in Riau -Indonesia - Herlina, Herlina; Hadriana, Hadriana; Zulirfan, Zulirfan; Elmustian, Elmustian (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to determine the effect of using the Riau Malay cultural e-module on the understanding of self-identity values among high school students in Riau Province. The background of this research is the still low level of students' understanding of local cultural values due to the limited availability of contextual and interactive learning media. The method used is quasi-experimental with a pretest-posttest control group design. The research sample consists of high school students selected purposively. The instruments include a self-identity values comprehension test and a student response questionnaire toward the e-module. The results indicate that the use of the Riau Malay cultural e-module significantly enhances students' understanding of their self-identity values compared to conventional methods. Additionally, students responded positively to the interactive e-module containing local cultural content. In conclusion, the Riau Malay cultural e-module is effective as a learning medium to strengthen the self-identity values of high school students in Riau Province. The implication of this study encourages the broader development of locally-based cultural teaching materials in the school environment.